23rd Annual Meeting of the German Society for Newborn Screening (Deutsche Gesellschaft für Neugeborenenscreening, DGNS) - Gwendolyn Gramer; Jürgen G. Okun; Georg F. Hoffmann (MDPI AG, 2016)
From 3-4 June, 2016, the 23rd Annual Meeting of the German Society for Newborn Screening (Deutsche Gesellschaft für Neugeborenenscreening, DGNS) was held at the University Hospital Heidelberg. The meeting was organized by PD Dr. med. Gwendolyn Gramer (conference president) from the Newborn Screening Centreat the University Hospital Heidelberg, Centre for Paediatric and Adolescent Medicine. Prof. Dr. med. Prof. h.c. mult. (RCH) Georg F. Hoffmann, PD Dr. phil. nat. Jürgen G. Okun and PD Dr. med. Gwendolyn Gramer formed the scientific board for the selection of presentations. Abstracts of plenary lectures, oral communications, and posters presented during the meeting are collected in this report.